2016
DOI: 10.1038/ncomms13511
|View full text |Cite
|
Sign up to set email alerts
|

Work extraction from quantum systems with bounded fluctuations in work

Abstract: In the standard framework of thermodynamics, work is a random variable whose average is bounded by the change in free energy of the system. This average work is calculated without regard for the size of its fluctuations. Here we show that for some processes, such as reversible cooling, the fluctuations in work diverge. Realistic thermal machines may be unable to cope with arbitrarily large fluctuations. Hence, it is important to understand how thermodynamic efficiency rates are modified by bounding fluctuation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…In [32,33], the work statistics in the scenario of a random quantum quench are computed, and it is shown that the knowledge of the work statistics in this setting yields information on the Loschmidt echo dynamics. The importance of work fluctuations in quantum thermodynamics in a different setting than ours was also studied in [34]. In this paper, we set out to study the scenario in which one gives the Hamiltonian H(t) for a specific model then it randomizes it by rotations.…”
mentioning
confidence: 89%
“…In [32,33], the work statistics in the scenario of a random quantum quench are computed, and it is shown that the knowledge of the work statistics in this setting yields information on the Loschmidt echo dynamics. The importance of work fluctuations in quantum thermodynamics in a different setting than ours was also studied in [34]. In this paper, we set out to study the scenario in which one gives the Hamiltonian H(t) for a specific model then it randomizes it by rotations.…”
mentioning
confidence: 89%
“…Recently, the problem of extracting work from a quantum system has received much attention [15,[17][18][19][20][28][29][30]. To demonstrate the advantage of the bittery, we apply it to study the work extraction problem in the single-shot regime.…”
Section: Application To Single-shot Work Extractionmentioning
confidence: 99%
“…Three work extraction schemes (or work contents) have been considered previously; however there is no general agreement on the maximum extractable work. The ε-deterministic work is the amount of deterministic work that can be extracted with failure probability ε [15,18,20,28], the ε-deterministic c-bounded work (or (ε, c)-deterministic work) is the ε-deterministic work with inherent fluctuations bounded by a given amount c [18][19][20]28], while the ε-guaranteed work is the work that is guaranteed to be exceeded with failure probability ε [29]. Following Refs.…”
Section: Application To Single-shot Work Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the above discussion implies that work should be defined with an experimental setup in mind, fundamental limits can be obtained. The question of how much work can be extracted from a quantum state has received a lot of attention recently [35,37,42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] and lies at the heart of the resource theory of quantum thermodynamics [5,35,37,49,51,56,[58][59][60][61][62][63][64]. As these works consider very abstract and general settings (hence assuming essentially full control over the system) it is not clear that the fundamental bounds are relevant in an experimental setting.…”
Section: Introductionmentioning
confidence: 99%